Integrated monitoring and managing system for middle and low voltage distribution network - WU LIUYI; TIAN YU; BA GENNA; YANG FEIYONG; LI ZHIKUN (2018)
The invention discloses an integrated monitoring and managing system for a middle and low voltage distribution network. The integrated monitoring and managing system comprises an intelligent data collection terminal, a data transmission module, a data processing module, a service module and a display module, wherein the intelligent data collection terminal transmits initial data to the data processing module through the data transmission module; the data processing module carries out real-time processing on the obtained data, generates cooked data capable of being recognized by the system andstores the cooked data into a real-time database; the service module provides the cooked data to the outside world and generates a real-time state of the distribution network and a real-time alarm oran event record according to the cooked data; and the display module displays the cooked data in a form of an image or a video and provides a user with human-computer interaction with a managing function. The management level